Gambaran Dukungan Keluarga, Status Nutrisi dan Skala Nyeri pada Pasien Post Op Ca Mamae: A Descriptive Study: Family Support, Nutritional Status and Pain Scale in Postoperative Breast Cancer - nuryanti, Ria; Setyawati, Retno; Erna Melastuti (Jurnal Keperawatan Berbudaya Sehat, 2025)
Family support will have an impact on increasing self-confidence in breast cancer patients in facing the treatment process of their disease, this contributes to preventing a decrease in nutritional status and pain due to side effects of treatment such as surgical procedures in breast cancer patients. This study aims to determine the description of family support, nutritional status, and pain scale in post-breast cancer surgery patients at Bhakti Asih Brebes Hospital. This quantitative study uses a descriptive method with a cross-sectional approach. The population in this study were 85 post-breast cancer surgery patients at Bhakti Asih Brebes Hospital, sampling using purposive sampling technique obtained a sample size of 71 patients. The research instruments used were family support questionnaires, body weight, and verbal rating scale (VAS). Data analysis was carried out descriptively using frequency and percentage tables. The results showed that post-breast cancer surgery patients at Bhakti Asih Brebes Hospital had good family support, namely 57 patients (80.3%), normal nutritional status, namely 40 patients (56.3%), and moderate pain levels, namely 51 patients (71.8%). Post-operative breast cancer patients at Bhakti Asih Brebes Hospital have good family support, nutritional status within the normal range, and moderate pain levels. Further research can conduct analysis related to the variables in this study, such as conducting correlational analysis, or testing a method related to the variables in this study.